Agricultural social organizations in contemporary Uruguay: an approach based on associative territoriality - Ceroni Acosta, Mauricio (2024)
The current configuration of Latin American agrarian capitalism is expressed in the growth of the control of land and the commercialization of agricultural commodities, sustained by an increase in the degradation of basic natural resources and a decrease in the rural population and the number of workers. In this context, it is necessary to understand the political practice actions by social agricultural organizations concerning their material base, since changes in the existing territories have reshaped the associative relationships of these organizations. In this sense, this paper aims to present the main characteristics of social agricultural organizations in recent Uruguay under the conceptual perspective of associative territoriality. For this purpose, descriptive and interpretive research was used with a qualitative methodological design. Among the main results, the following stand out: i) the agrarian associative territoriality in predominant contemporary Uruguay refers to rural development societies and farming cooperatives, ii) such territoriality is concentrated in the central-southern region of the country, and iii) the predominance of associative territoriality refers to low intensity.